Determinants of abdominal aortic aneurysm sac enlargement after endovascular aneurysm repair with a long-term follow-up to 15 years - Othman, Ahmad Faidzal (The Society For Vascular Surgery, 2012)
Studies have documented abdominal aortic aneurysm (AAA) enlargement in up to 41% of patients 5 years after endovascular repair (EVAR). Noting limitations of patient selection and length of follow-up, the current analysis was undertaken to assess AAA enlargement in an unselected patient cohort with follow-up for up to 15 years after repair.